A case-control study of reaction time deficits in a 3D virtual reality in patients with Post-COVID syndrome - Güttes, Moritz; Lucio, Marianna; Skornia, Adam; Rühl, Eva; Steußloff, Fritz; Zott, Julia; Mardin, Christian; Mehringer, Wolfgang; Ganslmayer, Marion; Michelson, Georg; Hohberger, Bettina (Scientific Reports, 2024)
Following the Coronavirus disease 2019 (COVID-19) pandemic, a large number of people continue to report Post-COVID symptoms (PCS). A wide variety of symptoms are described, including fatigue, post-exertional malaise and cognitive impairment. However, adequate objective diagnostic tests for PCS are not yet available. Since the neurotropism of SARS-CoV-2 could be a possible factor for cognitive impairment, the aim of this study was to clarify whether visual reaction time (RT) in a stereoscopic setting can be a marker in PCS diagnostics. The Virtual-Reality-Oculomotor-Test-System (VR-OTS) was used testing binocular vision in 9 gaze directions via stereoscopic stimuli displayed in a virtual reality (VR)-environment (disparity: 275″, 550″, 1100″) in 179 individuals: 130 patients with PCS and 49 healthy controls. The results from the generalized linear models indicated that both group membership (PCS vs. control) and covariates (age and sex) yielded statistically significant different RT across the models. Accounting for the effect of covariates a statistically significant difference of RT was observed between patients with PCS and controls (disparity 275″ p-value = 0.001; 550″ p-value = 0.001; 1100″ p-value = 0.003). Patients with PCS performed worse in RT in all gaze directions, respectively. Adjusting for the influence of covariates, correct responses (CR) differed significantly between patients with PCS and controls (disparity 275″ p-value < 0.001; 550″ p-value = 0.003; 1100″ p-value = 0.019). Statistically significant effects of covariates on RT were observed for sex (disparity 275″ p-value = 0.047; 550″ p-value = 0.012; 1100″ p-value = 0.005) and age (disparity 275″ p-value < 0.001; 550″ p-value < 0.001; 1100″ p-value < 0.001). However, regarding covariates, no significant effects were found for CR, except for age at disparity 275″ (p-value = 0.035). The present data suggested that the mentioned variables uniquely contributed to explain the variation of the response variable (RT, CR). RT and CR detecting 3D-stimuli in a virtual 3D- environment might offer novel functional diagnostic approaches in PCS.
CRIS-Team Scopus Importer:2024-11-29

Bilateral Acute Macular Neuroretinopathy (AMN) after COVID-19 and its Clinical Course - Bartsch, Alexander; Skornia, Adam; Mardin, Christian Y.; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2023)
Acute macular neuroretinopathy (AMN) is a rare disease entity. It is mainly observed in young women with a history of influenza-like infection or who have been taking oral contraceptives for several years. Patients typically describe subjective visual deterioration and mono- or bilateral paracentral relative scotomas. In some cases, funduscopic ophthalmic examination may reveal subtle sharply demarcated flat lesions of reddish-brown or orange colour in the macular region. Diagnosis is usually made by near-infrared fundus imaging which shows hyporeflective areas, and SD-OCT imaging which manifests changes in the outer retinal layers. In the following, three patient cases with bilateral AMN are described which occurred in direct temporal relationship to a recent SARS-CoV-2 infection.
CRIS-Team WoS Importer:2023-06-02
Keywords: akute makuläre; Neuroretinopathie; SD-OCT; Retina; COVID-19; SARS-CoV-2

Post-COVID-19 Syndrome: Retinal Microcirculation as a Potential Marker for Chronic Fatigue - Schlick, Sarah; Lucio, Marianna; Wallukat, Gerd; Bartsch, Alexander; Skornia, Adam; Hoffmanns, Jakob; Szewczykowski, Charlotte; Schröder, Thora; Raith, Franziska; Rogge, Lennart; Heltmann, Felix; Moritz, Michael; et al. (International Journal of Molecular Sciences, 2022)
Post-COVID-19 syndrome (PCS) is characterized by persisting sequelae after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). PCS can affect patients with all COVID-19 disease severities. As previous studies have revealed impaired blood flow as a provoking factor triggering PCS, it was the aim of the present study to investigate the potential association between self-reported chronic fatigue and retinal microcirculation in patients with PCS, potentially indicating an objective biomarker. A prospective study was performed, including 201 subjects: 173 patients with PCS and 28 controls. Retinal microcirculation was visualized by OCT angiography (OCT-A) and quantified using the Erlangen-Angio-Tool as macula and peripapillary vessel density (VD). Chronic fatigue (CF) was assessed according to the variables of Bell’s score, age and gender. VDs in the superficial vascular plexus (SVP), intermediate capillary plexus (ICP) and deep capillary plexus (DCP) were analyzed, considering the repetitions (12 times). Seropositivity for autoantibodies targeting G protein-coupled receptors (GPCR-AAbs) was determined by an established cardiomyocyte bioassay. Taking account of the repetitions, a mixed model was performed to detect possible differences in the least square means between the different groups included in the analysis. An age effect in relation to VD was observed between patients and controls (p < 0.0001). Gender analysis showed that women with PCS showed lower VD levels in the SVP compared to male patients (p = 0.0015). The PCS patients showed significantly lower VDs in the ICP as compared to the controls (p = 0.0001 (CI: 0.32; 1)). Moreover, considering PCS patients, the mixed model revealed a significant difference between those with chronic fatigue (CF) and those without CF with respect to VDs in the SVP (p = 0.0033 (CI: −4.5; −0.92)). The model included variables of age, gender and Bell’s score, representing a subjective marker for CF. Consequently, retinal microcirculation might serve as an objective biomarker in subjectively reported chronic fatigue in patients with PCS.
CRIS-Team Scopus Importer:2022-12-09
Keywords: chronic fatigue; chronic fatigue syndrome; COVID-19; functional GPCR autoantibodies; long COVID syndrome; OCT angiography; post-COVID-19 syndrome; retinal microcirculation